Breast Filariasis as Breast Abscess: A Rare Case Study from an Endemic Region - Vaibhav R.Gopal; Surender Kumar; Faraz Ahmad; Mithlesh Bhargav; Riddhi Jaiswal (Disease and Health: Research Developments Vol. 7, 2025)
Filariasis is a common infectious disease in tropical countries. In India, it is highly endemic in the states of Bihar, Kerala and Uttar Pradesh. Common sites of involvement in filariasis are lower limbs and the genitourinary region but rarely, it has been found in the thyroid, pleura, and pericardium. The Breast is an unusual site for filariasis and very few such cases have been reported to date. Clinically it can present as a lump which easily mimics inflammatory carcinoma (of the) breast. A thirty-two-year-old female presented with a painless progressive lump in the right breast with intermittent high-grade fever for 10 days. No other symptoms were present. She was non-diabetic and non-hypertensive with insignificant family and menstrual history. On examination, there was a tender freely mobile lump of approximately 5×4 cm occupying the lower inner quadrant (of the right breast) having firm consistency and a centre fluctuant area of 1 cm, the overlying skin was erythematous. A single non-tender mobile lymph node was present in the right axilla. The contralateral breast (i.e. left breast) was clinically normal. High-resolution sonography revealed cystic lesions from 3-6 O’clock position and axillary lymphadenopathy. The fine needle aspiration cytology showed microfilariae. Hence, a diagnosis of breast filariasis was made. Fluid aspirated from the cavity came out to be sterile. The patient improved symptomatically on di-ethyl-carbazine citrate (DEC) therapy (6 mg/kg for 2 weeks) and the lump too regressed in size. In conclusion, Filariasis in the Breast is very rare, with no specific signs. Histo-pathological test (FNAC/biopsy) is necessary for confirmation. Permanent lymphatic damage can cause irreversible lymphedema. Hence, proper counselling for chronic complications is very essential.